Peran PT Permodalan Nasional Madani Mekaar Syariah dalam Pemberdayaan Pedagang Perempuan (Studi Kasus PNM Mekaar Syariah di Komplek Padang Sarai Pratama, Kecamatan Koto Tangah, Kota Padang) - Sapitri, Yella; Puteri, Hesi Eka (ARZUSIN, 2026)
Women’s empowerment in the microeconomic sector has received attention in various studies, but research specifically examining the role of Islamic financial institutions in empowering female traders based on Longwe analysis remains limited. This study aims to analyze the role of PT Permodalan Nasional Madani (PNM) Mekaar Syariah in empowering female traders in Padang Sarai Pratama Complex, Koto Tangah Subdistrict, Padang City. This study used a qualitative approach with a case study design, involving female customers and field officers as participants selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and were then analyzed using the interactive analysis technique of Miles, Huberman, and Saldaña as well as the Longwe analysis approach. The results showed that PNM Mekaar Syariah played a significant role in empowering female traders through collateral-free financing and group-based business assistance. This program had an impact on improving women’s welfare, access to resources, critical awareness, participation, and control in economic activities. However, its implementation still faced obstacles in the form of a lack of discipline in installment payments and limited business management among some customers. The conclusion of this study affirms that the integration of sharia financing and business assistance is an important factor in strengthening women’s economic empowerment. These findings contribute to the development of studies on women’s empowerment based on Islamic economics and provide practical implications for Islamic financial institutions to improve education, assistance, and customer capacity building in microenterprise development.